Behçet disease: do individual symptomatology or certain drug intake reflect the severity of sensory neural hearing loss? - Dina Osman; Mervat Bahiri; Noha Hassan; Yumn Elsabbagh (Egyptian Rheumatology and Rehabilitation)
Abstract Background Behçet disease is a relapsing, chronic, systemic inflammatory illness characterized by mucocutaneous, articular, neurological, urogenital, vascular, intestinal, and pulmonary symptoms in addition to recurrent aphthous stomatitis, genital ulcerations, and ophthalmic disease. Objectives Assessing effect of disease symptomatology and drugs used on sensorineural hearing loss severity. Methods In this study, 60 adult Behçet disease patients participated. All underwent a comprehensive medical history, a basic audiological assessment, a Behçet disease current activity form, and a tinnitus handicap inventory scale. Results Sixty percent of the participants, had sensorineural hearing loss; over half (55.6%) had mild sensorineural hearing loss, there is no statistically significant correlation between the duration, the Behçet disease current activity form score, the tinnitus handicap inventory scale, vascular symptoms, and sensorineural hearing loss. Conclusions Prevalence of sensorineural hearing loss is 60%. Auditory manifestations and hemoglobin (HB) level are independent factors for sensorineural hearing loss (SNHL), no relation between disease manifestation, duration, disease activity, drugs and severity of hearing loss, no relation between level of platelets, HB, total leukocyte count (TLC), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and severity of hearing loss.